2012
DOI: 10.1002/app.37794
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural characterization of corn starch‐based porous thermoplastic composites filled with multiwalled carbon nanotubes

Abstract: Microstructural characterization of corn starch-based porous thermoplastic (TPS) composites containing various contents (0.1, 0.5, and 1 wt %) of multiwalled carbon nanotubes (MWCNTs) was performed. Corn starch was plasticized with a proper combination of glycerol and stearic acid. TPS composites with MWCNT were prepared conducting melt extrusion followed by injection molding. TPS containing 1 wt % of MWCNTs exhibited higher tensile strength and elastic modulus values than neat TPS. Moreover, TPS electrical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
3
10
1
Order By: Relevance
“…In polymer matrices, usually nanoparticles play a double role: on the one hand, when they are below the percolation concentration act as nucleating agents to enhance the crystallization; on the other hand, when this concentration exceeds, they act as a barrier to retard the crystallization (Xu et al, 2010). According to the literature, carbon nanotubes have a peak at 24 ° (Yurdakul et al, 2013); however, this peak was not observed in our work. This could be due to the low concentration of filler used.…”
Section: Densitycontrasting
confidence: 81%
“…In polymer matrices, usually nanoparticles play a double role: on the one hand, when they are below the percolation concentration act as nucleating agents to enhance the crystallization; on the other hand, when this concentration exceeds, they act as a barrier to retard the crystallization (Xu et al, 2010). According to the literature, carbon nanotubes have a peak at 24 ° (Yurdakul et al, 2013); however, this peak was not observed in our work. This could be due to the low concentration of filler used.…”
Section: Densitycontrasting
confidence: 81%
“…Biocomposite film gives the peaks at 2θ values of 12.24° and 19.92°. These peaks are characteristic crystalline peaks for thermoplastic starch …”
Section: Resultsmentioning
confidence: 99%
“…Starch is a natural renewable polysaccharide and exists in the form of fine white granules composed of amylose and amylopectin accompanied by the basic composite unit of glucose. Starch has been cited as one of the most promising renewable source‐based polymers owing to its large scale of availability and low cost . However, especially following aging, starch‐based polymers are sensitive to moisture and becomes brittle compared with typical synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The additives were added up to 3 % in weight, while water up to 5 % in weight. Yurdakul et al (2013), proposed to mix starch, carbon nanotubes, water and glycerol, gelatinize the obtained suspension and introduce it manually into the extruder. Hietala et al (2013), premixed starch, plasticizer, lubricant, and cellulose nanofiber (C-NF) gels with high water contents and then extruded the obtained dispersions.…”
Section: Extrusionmentioning
confidence: 99%